HUBUNGAN PELAKSANAAN MANAJEMEN LAKTASI DENGAN PARITAS IBU MENYUSUI DI PMB HUSNIYATI TAHUN 2024 - Emilda, Sri; Qudratullah, Fyzria; Putri Rahmah Azzahrah (LPPM STIKes Mitra Adiguna, 2025)
Lactation management is a procedure that regulates the entire breastfeeding process to run well. Other factors that also influence a mother's failure to provide exclusive breastfeeding are perinatal factors (parity and type of delivery). The purpose of this study was to determine the relationship between the implementation of lactation management and the parity of breastfeeding mothers at PMB Husniyati in 2024. This research method uses an analytical method with a cross-sectional approach with a sample size of 35 people. Based on the results of the research that has been carried out regarding the relationship between the implementation of lactation management and the parity of breastfeeding mothers, the results obtained from the bivariate analysis of the chi-square statistical test show that the p value = 0.04 (? 0.05). The conclusion is that there is a relationship between the implementation of lactation management and the parity of breastfeeding mothers at PMB Husniyati Palembang in 2024. Suggestions are expected for health workers, especially midwives, to provide counseling on the implementation of lactation management that is adjusted to the parity of breastfeeding mothers.